Obesity and Lung Disease A Guide to Management - Dixon, Anne E.; Clerisme-Beaty, Emmanuelle M. (Respiratory Medicine,, 2013)
As a result of the rapidly growing rate of obesity worldwide, clinicians are struggling to provide the best strategies for treating obese patients with concomitant pulmonary conditions. Obesity does not simply change the epidemiology of pulmonary disease; obesity has a profound impact on the pathophysiology of common pulmonary diseases. Obesity affects the severity of asthma, response to treatment, and is likely a major modifier of the phenotype of asthma. Obesity also appears to affect response to pathogens, and as such has a major influence on response to pneumonia, and has a significant impact on outcomes pertaining to acute lung injury in the intensive care unit. Obesity and Lung Disease: A Guide to Management is the first text in the field to cover the full range of issues related to managing obese patients with pulmonary problems. All the relevant conditions, in the context of obesity, are covered, including airway inflammation, sleep apnea, asthma, pulmonary hypertension, obesity hypoventilation, as well as others. Written by an international group of experts, this important new volume is an invaluable resource for all clinicians and scientists concerned with the challenging problems surrounding obesity and lung diseases.  .